Adherence to aerobic and muscle-strengthening activities guidelines: a systematic review and meta-analysis of 3.3 million participants across 32 countries. (23rd November 2022) - Garcia-Hermoso, Antonio; López-Gil, José Francisco; Ramírez-Vélez, Robinson; Alonso-Martínez, Alicia María; Izquierdo, Mikel; Ezzatvar, Yasmin
Abstract : Objective: To estimate the global prevalence of meeting the WHO guidelines for both aerobic and muscle-strengthening activities (MSA) in populations aged ≥5 years, and whenever possible to explore this prevalence according to sociodemographic and lifestyle factors. Design: A systematic review and meta-analysis. Data sources: Five databases were systematically searched for studies published from inception to September 2022. Eligibility criteria for selecting studies: Articles with representative samples aged ≥5 years reporting the prevalence of meeting both aerobic and MSA guidelines were included. Results: Twenty-one studies comprising 3 390 001 individuals from 32 countries were included. Overall adherence to the aerobic and MSA guidelines was 17.12% (95% CI 15.42% to 18.88%) in adults ≥18 years (n=3 346 723). Among adolescents aged 12–17 years, adherence to both guidelines was 19.74% (95% CI 14.72% to 25.31%) (n=43 278). No studies reported data for children aged 5–11 years. Women, older age, low/medium education levels, underweight or obesity, and poor and moderate self-rated health were associated with lower adherence to the physical activity guidelines (p<0.001) among adults, although the prevalence remained very low in all cases. Subgroup analyses were not conducted with children and adolescents due to a lack of studies. Conclusions: Only one out of five adolescents and adults met the recommended combined aerobic and MSA guidelines. Large-scale public health interventions promoting both types of exercise are needed to reduce the associated burden of non-communicable diseases. PROSPERO registration number: CRD42022338422.